MC/DC COVERAGE FOR REQUIREMENTS SPECIFICATIONS - Das, Gourav (East Carolina University, 2018)
In the early 1990s, the Modi ed Condition/Decision Coverage (MC/DC) criterion was suggested as a structural white-box testing approach, but it can also be used for blackbox speci cation-based testing. Practical application of MC/DC for speci cationbased testing has its own unique features and is sometimes quite di erent from codebased applications. However, MC/DC as a black-box approach has not been studied su ciently, and thus, the application of MC/DC for speci cation coverage was the main research problem considered in this thesis. The goal of this study was to analyze MC/DC as a black-box technique, investigate factors that distinguish black- and white-box applications of this approach, and provide proper de nitions and rules with a prototype implementation to evaluate the MC/DC level during black-box testing.
Keywords: MC/DC; Computer software--Testing